In vitro transfection potential of fluorinated G5 PAMAM dendrimers for miRNA delivery to MRC-5 cells - Öztuna, Ali; Nazır, Hasan (The European Research Journal, 2018)
Objectives. MicroRNAs (miRNAs) are involved in the regulation of most biological processes and also contribute to many types of disease. Fibroblast cells, such as MRC-5, are often used in biological researches utilizing cell transfection methods due to their difficult to transfect nature. Cells can be genetically engineered by using viral and non-viral methods. Poly(amidoamine) (PAMAM) dendrimers are very promising alternative as a delivery vehicle due to their well-defined characteristics. In this study, in vitro transfection potential of cystamine core generation five (G5) PAMAM dendrimers fluorinated with 2,3,4,5,6-pentafluorobenzoic acid (PFB) and pentafluoropropionic acid (PFP) for miRNA delivery to MRC-5 cells was examined.Methods. Spectroscopic techniques were used in the characterization of the prepared dendrimers. miRNA binding and condensation capability of dendrimers was examined by gel retardation assay. Characterization of dendriplexes was made by zeta potential, particle size measurements and transmission electron microscopy. Transfection efficiencies of the dendriplexes were determined by flow cytometry and intracytoplasmic distribution of the dendriplexes was shown by laser scanning confocal microscopy. Also, quantitative structure-activity relationship and molecular docking calculations were used to be able to discuss transfection efficiencies of the dendriplexes into the cell.Results. While high level of viability on MRC-5 cells was observed for dendriplexes prepared with PFB and PFP, transfection efficiency with PFP was higher than PFB. Transfection efficiency difference between these two compounds was attributed to their molecular structures.Conclusions. Obtained results hold promise for the usage of these compounds as a transfection reagent at MRC-5 cells. Further studies are needed to support these findings.